PENGGUNAAN METODE SAS (STRUKTURAL ANALITIK SINTETIK) DALAM PEMBELAJARAN BAHASA INDONESIA MENULIS PERMULAAN SISWA SEKOLAH DASAR - Dewi, Candra (BAHASTRA, 2018)
This study aims to determine the implementation of the use of SAS (Structural Analytic Synthetic) method in Indonesian language learning to write the beginning of elementary school students. This research is a qualitative descriptive research. Subjects in this research are first grade teachers of Elementary School and Elementary School students of 20 students. In this study researchers used data collection techniques by way of observation, documentation, interviews and tests. Data analysis technique in this research is interactive data analysis, there are three main thing in data analysis of interactive model that is data reduction, data presentation, and conclusion. Based on the implementation of SAS method in Indonesian Language subjects to train writing skill in grade 1 students of SD 2 Negeri Bendo Subdistrict, Magetan Regency has been running in accordance with the learning plan as stated in the lesson planning plan. given the result of writing the student is good enough The average grade of 81.75 from 20 students in class I. the lowest value yiatu 70 and the highest value is 90. Based on the predetermined KKM that is 75, it can be concluded that there is 90% students have achieved the value or achieved the value of KKM, while 10% of students still have not reached the value of complete or still below the value of KKM.